2009
DOI: 10.1123/jsr.18.3.375
|View full text |Cite
|
Sign up to set email alerts
|

Altered Ankle Kinematics and Shank-Rear-Foot Coupling in Those with Chronic Ankle Instability

Abstract: Altered ankle kinematics and joint coupling during the terminal-swing phase of gait may predispose a population with CAI to ankle-inversion injuries. Less coordinated movement during gait may be an indication of altered neuromuscular recruitment of the musculature surrounding the ankle as the foot is being positioned for initial contact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
119
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(129 citation statements)
references
References 28 publications
6
119
3
1
Order By: Relevance
“…Increased rearfoot inversion has been reported before, at and immediately after initial contact (IC) during walking, throughout the gait cycle during walking and jogging, and in the pre landing phase of running [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Increased rearfoot inversion has been reported before, at and immediately after initial contact (IC) during walking, throughout the gait cycle during walking and jogging, and in the pre landing phase of running [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to healthy subjects, CAI patients have been found to have a more laterally situated center of pressure during gait [69,70]. More complex analysis of movement has found more sensitive alterations in joint coupling around the ankle [47]. Drewes et al [47] and McKeon et al [71] identified changes in the relationship of shank transverse motion and rearfoot inversion and eversion.…”
Section: Sensorimotor Function and Ankle Instabilitymentioning
confidence: 99%
“…More complex analysis of movement has found more sensitive alterations in joint coupling around the ankle [47]. Drewes et al [47] and McKeon et al [71] identified changes in the relationship of shank transverse motion and rearfoot inversion and eversion. The analysis of joint coupling may further expand on central changes associated with coordinating gait in subjects with CAI.…”
Section: Sensorimotor Function and Ankle Instabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…18 Ankle-dorsiflexion deficits 9 and increased subtalar-inversion and shank external-rotation ranges of motion have been demonstrated during both walking and jogging in CAI patients compared with healthy control participants. 19 Altered muscle function after joint injury has been hypothesized to have neural origins rooted partially in a clinical impairment known as the arthrogenic muscle response. 20 This impairment is characterized by an abnormal facilitation or inhibition of neural drive to the undamaged musculature surrounding an injured joint.…”
mentioning
confidence: 99%